Terror Capitalism : Uyghur Dispossession and Masculinity in a Chinese City - Byler, Darren (Book collections on Project MUSE., 2021)
"Darren Byler theorizes the contemporary Chinese colonization of the Uyghur Muslim minority group in the northwest autonomous region of Xinjiang, showing how it has led to what he calls terror capitalism--a configuration of ethno-racialization, surveillance, and mass detention that in this case promotes settler colonialism."--